Parameter optimization and test of hydraulic soil insertion device of orchard gas explosion subsoiling and fertilizing machine - Shen, Congju; Zhang, Lixin; Jia, Shouxing; Zhou, Yan; Li, Fan; Dai, Yameng; Zhang, Jing; Ma, Wenxiao (International Journal of Agricultural and Biological Engineering, 2023)
Hydraulic soil insertion device is a key component of orchard gas explosion subsoiling and fertilizing machine to realize rod fixed point soil insertion and gas fertilizer injection into soil. In order to explore the influence of the main working parameters and structural parameters on the depth and cylinder pressure of the hydraulic insertion device during the insertion process, the working parameters were optimized to ensure the insertion quality and efficiency. In this paper, force analysis was performed on the rod insertion process, and key parameter equation of soil insertion resistance was established. LS- DYNA finite element simulation software was applied to analyze the force variation of the rod during the insertion process. Box-Behnken test optimization design method and Design-Expert V8.0.6.1 software were used to carry out parameter optimization test of hydraulic insertion device. A multivariate quadratic polynomial regression equation was established by setting the engine revolution, insertion rod diameter and insertion time as independent variables, and the operation parameters of the hydraulic insertion device were optimized based on the relationship between the independent variables and the response values. The results showed that the regression equation model based on the response values of insertion depth and cylinder pressure had a good fitting degree. The engine revolution, rod diameter and insertion time all had significant effects on the increase of insertion depth and decrease of cylinder pressure, with interaction between the engine speed and insertion time with the insertion depth, and interaction between any two factors of engine revolution, rod diameter and insertion time with the cylinder pressure. The influences of the test factors on the insertion depth showed a descending order as engine speed, insertion time, and rod diameter. The influences of the test factors on the cylinder pressure showed a descending order as engine speed, rod diameter, and insertion time. Based on the results of insertion depth and cylinder pressure, the optimal combination of parameters was as follows: engine revolution of 1450 r/min; rod diameter of 32 mm; and the insertion time of 8 s. Under this optimal combination, the insertion depth of the hydraulic insertion device was 44.43 cm, and the cylinder pressure was 23.09 MPa. The experimental results showed that the optimal combination of parameters could meet the agronomic requirements of fast and deep insertion, thus providing a theoretical support for the improvement and optimization of hydraulic soil insertion device of gas explosion subsoiling and fertilizing machine.Key words: orchard management machinery, subsoiling, gas explosion, fertilization, hydraulic insertion, optimizationDOI: 10.25165/j.ijabe.20231602.7126Citation: Shen C J, Zhang L X, Jia S X, Zhou Y, Li F, Dai Y M, et al. Parameter optimization and test of hydraulic soil insertion device of orchard gas explosion subsoiling and fertilizing machine. Int J Agric & Biol Eng, 2023; 16(2): 132–141.